Luminescence detection of latent fingermarks on non-porous surfaces with heavy-metal-free quantum dots - Shahbazi, Sorour; Boseley, Rhiannon; Grant, Braden; Chen, Dechao; Becker, Thomas; Adegoke, O.; Nic Daéid, N.; Jia, Guohua; Lewis, Simon (ELSEVIER, 2020)
Current and proposed nanoparticle-based techniques for development of latent fingermarks suffer a number of drawbacks such as complicated, multi-step and time-consuming procedures, batch-to-batch variability, expensive reagents, large background noise and toxicity. Here, we introduce a promising green development technique based on heavy-metal-free quantum dots for the detection of latent fingermarks on non-porous surfaces. Red-near infrared luminescent CuInS2/ZnS core/shell quantum dots in aqueous solution were produced in large scales using a simple, fast, water-based method with N-acetylcysteine as a biocompatible surfactant to coat the particles. The coated quantum dots were applied to the successful development of latent fingermarks deposited on a variety of surfaces, including highly patterned polymer banknotes and the sticky side of adhesive tape.